Zwitterionic mesoporous nanoparticles with a bioresponsive gatekeeper for cancer therapy. (August 2016) - Khatoon, Shakera; Han, Hwa Seung; Lee, Minchang; Lee, Hansang; Jung, Dae-Woong; Thambi, Thavasyappan; Ikram, M.; Kang, Young Mo; Yi, Gi-Ra; Park, Jae Hyung
Graphical abstract: Abstract: To enhance cellular uptake and site-specific drug release in the tumor microenvironment, zwitterionic mesoporous silica nanoparticles (Z-MSN) were prepared by introducing a bioresponsive gatekeeper composed of negatively charged carboxylic groups and positively charged quaternary amine groups. When these Z-MSN encountered a mildly acidic environment, their surface charge readily switched from negative to positive by cleavage of an acid-labile maleic amide linkage, thus allowing for effective cellular uptake into tumor tissue. Doxorubicin (DOX) encapsulated in Z-MSN was not significantly released in physiological conditions (pH 7.4), whereas the release rate of DOX remarkably increased in mildly acidic conditions through disintegration of the gatekeeper. The antitumor efficacy of DOX-loaded Z-MSN (DOX-Z-MSN) was evaluated after their systemic administration to tumor-bearing mice. Compared to free DOX and DOX-loaded MSN without the gatekeeper, DOX-Z-MSN exhibited much higher antitumor efficacy in vivo . Overall, these results demonstrated that the hydrophilic negative surface of Z-MSN, with their closed gate, allowed for their effective accumulation in tumor tissue after systemic administration, and that their charge-swapping and gate-opening in the tumor environment enhanced their cellular uptake and drug release rate simultaneously, implying a highly promising potential for development of Z-MSN as a drug carrier for cancer therapy. Statement of Significance: In an attempt to address the issues of enhanced cellular uptake and site-specific drug release of nanoparticles, we herein report on zwitterionic MSN (Z-MSN) with a pH-responsive gatekeeper which can be internalized into cancer cells via switching their surface charge from negative, in physiological conditions, to positive, in the tumor microenvironment. We hypothesized that the hydrophilic negative surface of Z-MSN with a closed gate allows for their accumulation into tumor tissue after systemic administration, whereas their charge-swapping and gate-opening in the tumor environment enhance cellular uptake and drug release rate simultaneously. Overall, Z-MSN constitute a promising drug delivery carrier for cancer therapy.